Replacing Animal Protein with Soy-Pea Protein in an "American Diet" Controls Murine Crohn Disease–Like Ileitis Regardless of Firmicutes: Bacteroidetes Ratio. Issue 3 (20th January 2021) - Raffner Basson, Abigail; Gomez-Nguyen, Adrian; LaSalla, Alexandria; Buttó, Ludovica; Kulpins, Danielle; Warner, Alexandra; Di Martino, Luca; Ponzani, Gina; Osme, Abdullah; Rodriguez-Palacios, Alexander; Cominelli, Fabio
ABSTRACT: Background: The current nutritional composition of the "American diet" (AD; also known as Western diet) has been linked to the increasing incidence of chronic diseases, including inflammatory bowel disease (IBD), namely Crohn disease (CD). Objectives: This study investigated which of the 3 major macronutrients (protein, fat, carbohydrates) in the AD has the greatest impact on preventing chronic inflammation in experimental IBD mouse models. Methods: We compared 5 rodent diets designed to mirror the 2011–2012 "What We Eat in America" NHANES. Each diet had 1 macronutrient dietary source replaced. The formulated diets were AD, AD-soy-pea (animal protein replaced by soy + pea protein), AD-CHO ("refined carbohydrate" by polysaccharides), AD-fat [redistribution of the ω-6:ω-3 (n–6:n–3) PUFA ratio; ∼10:1 to 1:1], and AD-mix (all 3 "healthier" macronutrients combined). In 3 separate experiments, 8-wk-old germ-free SAMP1/YitFC mice (SAMP) colonized with human gut microbiota ("hGF-SAMP") from CD or healthy donors were fed an AD, an AD-"modified, " or laboratory rodent diet for 24 wk. Two subsequent dextran sodium sulfate–colitis experiments in hGF-SAMP (12-wk-old) and specific-pathogen-free (SPF) C57BL/6 (20-wk-old) mice, and a 6-wk feeding trial in 24-wk-old SPF SAMP were performed. Intestinal inflammation, gut metagenomics, and MS profiles were assessed. Results: The AD-soy-pea diet resulted in lower histology scores [mean ± SD (56.1% ± 20.7% reduction)] in all feeding trials and IBD mouse models than did other diets ( P < 0.05). Compared with the AD, the AD-soy-pea correlated with increased abundance in Lactobacillaceae and Leuconostraceae (1.5–4.7 log2 and 3.0–5.1 log2 difference, respectively), glutamine (6.5 ± 0.8 compared with 3.9 ± 0.3 ng/μg stool, P = 0.0005) and butyric acid (4:0; 3.3 ± 0.5 compared with 2.54 ± 0.4 ng/μg stool, P = 0.006) concentrations, and decreased linoleic acid (18:2n–6; 5.4 ± 0.4 compared with 8.6 ± 0.3 ng/μL plasma, P = 0.01). Conclusions: Replacement of animal protein in an AD by plant-based sources reduced the severity of experimental IBD in all mouse models studied, suggesting that similar, feasible adjustments to the daily human diet could help control/prevent IBD in humans.